Návrh změn systému řízení identit ve firmě - Vokálek, Vojtěch (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Předmětem diplomové práce je prozkoumat integraci systému správy identit se systémem řízení bezpečnosti informací na základě teoretických poznatků a analýzy současného stavu. Upozornit společnost na nedostatky a podat návrhy na zlepšení.

The subject of the Master thesis is to explore the integration of Identity Management System with the Information Security Management System based on theoretical knowledge and analysis of the current situation. Notify the company to gaps and make proposals for improvement.
Draft of Changes Identity Management System in a Firm
Keywords: Identity management; ISMS; bezpečnost; proces; společnost; role; architektura; přístup; cyklus; heslo; Identity management; ISMS; security; process; company; role; architecture; access; cycle; password